Neogreenia lonicera sp. nov., a new species of Margarodidae sensu lato (Hemiptera: Coccoidea) from China, with a key to species of Neogreenia MacGillivray and placement of the genus in the family Kuwaniidae - Wu, San’an; Nan, Nan (Zootaxa, 2012)
A new species, Neogreenia lonicera Wu & Nan, is described and illustrated based on the adult female, second-instarfemale and first-instar nymph. This new species was collected at Helan Mountain, Inner Mongolia, China, in bark crevicesof Lonicera microphylla (Caprifoliaceae). A key is provided to separate the five species now known in NeogreeniaMacGillivray. A cladistic analysis of morphological data from adult females and first-instar nymphs of 28 archaeococcoidgenera has Neogreenia in a clade with Jansenus Foldi and Neosteingelia Morrison and usually also with KuwaniaCockerell, and thus Neogreenia should be placed in the family Kuwaniidae. A key to distinguish the adult females of the four genera of the Kuwaniidae is provided.